MEKANISME PROSES MUSYAWARAH PERENCANAAN PEMBANGUNAN PROVINSI DI KALIMANTAN BARAT - Susila Hernanti E.21107100 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This article aims to examine the mechanism / implementation phase of the Pre-Murenbang and Musrenbang RKPD on BAPPEDA Province of West Borneo Province in 2012. This article is classified as type of exploratory study with a qualitative approach. The data was collected by interview and observation. Informants were selected by purposive sampling method which officers and staff within the Bappeda West Borneo Province, located in the Planning Department of Economic, Social and Cultural Planning, Field Monitoring, Evaluation and Control, and Data Development Planning Unit. The results showed that: first, the implementation of the Pre-Musrenbang RKPD West Borneo Province in accordance with Law No. 32 Year 2004 on Regional Government, which the Government of West Borneo Province, through Bappeda have put through stakeholder participation as an essential element to achieve the goal welfare of the community; create a sense of community in local governance, and ensuring the presence of transparency, accountability and the public interest; formulation of programs and services that meet the aspirations of the general public in order to reconcile the interests and needs of local government and local non-governmental regional planning documents. Second, in its implementation, the implementation has Musrenbang according to the Law No. 25 Year 2004 on Regional Planning, where the regulation mandated that each municipality must prepare regional development plans in a systematic, purposeful, integrated and responsive to change, with the level of long-term planning, medium term and short term.Keywords: Mechanism Musrenbang; Pra Musrenbang and Implementation of Musrenbang.